P277 The environmental impact of wasteful procedures in two UK endoscopy units. (19th June 2022) - Sukthankar, Tanmay; Gurr, Vanya; Hoque, Sami; Watson, Alan; Dias, Aruna; Green, Cameron; Vinayaga-Pavan, Mathena; Maurice, James
Abstract : Introduction: The NHS is the first healthcare system to commit to carbon neutrality by 2045. There is increasing recognition that endoscopies make a significant contribution to the NHS carbon footprint, which must be assessed to develop a greener service. This study aims to identify the proportion of procedures and biopsies that could have been avoided, to inform changes that will increase sustainability. Methods: All procedures over 7 days in October 2021 within 2 endoscopy units were included. Relevant data - indication, referrer, biomarkers, blood tests, biopsies, and outcome - were collected for each case, and reviewed by two independent senior gastroenterologists to identify avoidable procedures and sampling. The carbon footprint of wasteful procedures was calculated using published data 1 2 and a publicly available calculator based on patient journey miles. 3 Results: 235 cases were analysed (gastroscopy 44%, flexible sigmoidoscopy 15%, colonoscopy 41%). Referrals were made by gastroenterology 23%, surgery 51%, medicine 8%, GP 14%, and specialist nurse 2-week-wait 4%. 43 (18%) procedures were deemed avoidable, of which 53% were colonoscopy, 42% gastroscopy, 5% flexible sigmoidoscopy. These referrals came from: surgery (63%), gastroenterology (19%), GP (9%) and medicine (7%). Common reasons for colonoscopies being inappropriate were incomplete biomarkers (35%), flexible sigmoidoscopy being more appropriate (30%), and non-iron deficient anaemia (IDA, 17%); for gastroscopies, low risk abdominal pain <55 years (60%) and non-IDA (40%). 82% of biopsies sent from colonoscopies were indicated compared to only 49% from gastroscopy ( figure 1 ). The estimated carbon footprint of wasteful procedures (including patient journeys, endoscopy, waste generation, and biopsy processing), was 233 kgCO2e/week; approximately 12 tCO2e/year (117 return economy flights from London to Paris 3 ). Conclusion: Avoidable endoscopies have a detrimental environmental impact. Rigorous vetting, and education on appropriate sampling in gastroscopy, will help mitigate this. 1. Siau, K., Hayee, B. H. & Gayam, S. Endoscopy's Current Carbon Footprint. Tech. Innov. Gastrointest. Endosc. 23, 344–352 (2021). 2. Gordon, I. O., Sherman, J. D., Leapman, M., Overcash, M. & Thiel, C. L. Life Cycle Greenhouse Gas Emissions of Gastrointestinal Biopsies in a Surgical Pathology Laboratory. Am. J. Clin. Pathol. 156, 540–549 (2021). 3. Carbon Footprint Calculator. Available at: https://calculator.carbonfootprint.com/calculator.aspx?tab=4. (Accessed: 14th February 2022)